ANALISIS HUBUNGAN REGULASI DAN SUMBER DAYA APARATUR PENGAWAS TERHADAP PENGAWASAN PENGELOLAAN KEUANGAN DAERAH - Arum Ardianingsih; Amalia Ilmiani (Jurnal Ekonomi Dan Bisnis, 2017)
Financial management a necessity in the era of regional autonomy. Supervision in the financimanagement of local government conducted by Inspectorate City. Government Regulation (PP) No. 6of 2008 states that the role of the Inspectorate is to conduct internal oversight, ie the whole process oaudit, review, evaluation, monitoring and supervisory activities other against the implementation otasks and functions of the organization in order to provide reasonable assurance to users of financistatements area. The purpose of this study is to provide empirical evidence that the regulatory an supervisory personnel resources affect the supervision of financial management. This study usevalidity and reliability, the classic assumption test and multiple linear regression analysis. Engineerinsamples using purposive sampling with 45 respondents government's internal auditor. The resulshowed that the Regulation and Supervisory Apparatus Resources significant influence on thsupervision of financial management.Keywords: regulation, supervisory personnel resources, supervision of financial management.